2017
DOI: 10.4028/www.scientific.net/amm.871.161
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Thermal and Fluid Mechanical Modeling of a High Speed Motor Spindle

Abstract: The objective of this survey is to evolve a better understanding of the complex thermal interactions inside a motor spindle. Therefore, the thermal behavior is investigated based on a simulation model and experiments. In contrast to existing simulation models, which either performed a complex thermal examination or an elaborate flow-mechanical analysis, a thermal (Finite Element Method) and fluid mechanical (Computational Fluid Dynamics) coupled simulation model was developed. Based on a comparative analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…2, right) was a Finite-Element-Model (FEM) with an additionally coupled Computational-Fluid-Dynamics (CFD) simulation for the fluid cooling systems inside the spindle housing. The first version of the spindle simulation model was based on a set of boundary conditions published in our previous works on a spindle with 18,000 rpm [3,18]. However, the empirical observation showed that this set of boundary conditions could not be conveyed to the test specimen of the analysis with 40,000 rpm.…”
Section: General Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…2, right) was a Finite-Element-Model (FEM) with an additionally coupled Computational-Fluid-Dynamics (CFD) simulation for the fluid cooling systems inside the spindle housing. The first version of the spindle simulation model was based on a set of boundary conditions published in our previous works on a spindle with 18,000 rpm [3,18]. However, the empirical observation showed that this set of boundary conditions could not be conveyed to the test specimen of the analysis with 40,000 rpm.…”
Section: General Approachmentioning
confidence: 99%
“…Figure 1 visualizes available models and their speed. Most publications [5][6][7][8][9][10][11][12][13][14][15][16][17][18] do not consider motorized spindles with more than 18,000 rpm. The recent addition of Denkana [19] showed modeling efforts for a spindle with 20,000 rpm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation